A new species of Niganda Moore, 1879 from Thailand, with descriptions of variation in male genitalia and female facies of N. radialis Moore (Lepidoptera: Notodontidae, Ceirinae) - Pellinen, Markku J.; Wahlberg, Niklas (Zootaxa, 2015)
Niganda phichai Pellinen, sp. n., is described from northern Thailand. The new species is diagnosed and illustrated, including details of the genitalia and DNA sequencing. Variability in the male genitalia of Niganda radialis Gaede is reviewed, and notes are presented on the facies of female N. radialis.